Central banking and monetary policy in the Asia-Pacific - Hossain, Akhand Akhtar (Edward Elgar, 2009)
Reviews the modern literature on inflation and monetary policy and highlights issues in the design and conduct of monetary policy for price stability in developing Asia. This work surveys the evolution of central banking and offers an introduction to the structure, function and governance of central banks in selected countries in the Asia-Pacific